Dampak Keberadaan PT. Abdi Budi Mulia Dalam Menjalankan Program Kemitraan Pekebun di Satuan Pemukiman di Kabupaten Labuhan Batu Selatan - Frenky Situmorang; Irvan Rolyesh Situmorang (Cattleya Darmaya Fortuna, 2024)
The palm oil smallholder partnership program is an initiative designed to support small oil palm farmers through partnerships with companies, and governments,. The main goal is to increase productivity, quality and welfare of small farmers while ensuring environmental sustainability. Company PT. Abdi Budi Mulia is a company engaged in palm oil plantations and processing factories. This company is implementing a partnership program in the South Labuhan Batu sub-district. This community service activity is intended to determine the impact of the existence of PT. Abdi Budi Mulia in carrying out partnership program activities in South Labuhan Batu. South Labuhan Batu Regency is one of the districts with good palm oil potential, especially in Kampung Rakyat. With the large area of ​​plantations in the area, good planning and processing is needed so that sustainable development can be realized, as well as improving community welfare. The problem that occurs in South Labuhan Batu is that the lack of education regarding palm oil plantations has resulted in the productivity of community-owned palm oil being lower compared to the productivity of company-owned (private) palm oil. This can be seen from the low price of community palm oil due to the quality of the owned palm oil. society is not very high